2021
DOI: 10.1186/s12974-021-02130-1
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy differentiates inflammatory from diabetic neuropathy

Abstract: Background Immune-mediated neuropathies, such as chronic inflammatory demyelinating polyneuropathy (CIDP) are treatable neuropathies. Among individuals with diabetic neuropathy, it remains a challenge to identify those individuals who develop CIDP. Corneal confocal microscopy (CCM) has been shown to detect corneal nerve fiber loss and cellular infiltrates in the sub-basal layer of the cornea. The objective of the study was to determine whether CCM can distinguish diabetic neuropathy from CIDP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…The corneal nerve fiber parameters might be a marker of axonal damage as well, but were not analyzed in this study since the longitudinal period of evaluation was very short and this parameters did not change (data not shown). Corneal nerve fiber reduction was shown in several types of neuropathy including immune-mediated neuropathies 26 28 , however acute upcoming disease activity was not analyzed in these studies. Taken together, both information, acute cell infiltration and axonal damage, are important but different aspects of the disease 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The corneal nerve fiber parameters might be a marker of axonal damage as well, but were not analyzed in this study since the longitudinal period of evaluation was very short and this parameters did not change (data not shown). Corneal nerve fiber reduction was shown in several types of neuropathy including immune-mediated neuropathies 26 28 , however acute upcoming disease activity was not analyzed in these studies. Taken together, both information, acute cell infiltration and axonal damage, are important but different aspects of the disease 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a potential immune‐mediated mechanism for small fibre loss has been proposed in patients with ATTRv neuropathy based on the observation that there was a clustering of immature Langerhans cells at the inferior whorl of the cornea in association with an early reduction in inferior whorl length. 27 In general, reduced CNFD represents axonal loss, while increased corneal cellular infiltration reflects inflammation 22 , 23 , 24 as the majority of morphologically dendritic corneal cells are indeed antigen presenting Langerhans cells. 36 , 37 , 38 , 39 In recent longitudinal studies, higher total corneal cell counts were associated with a more progressive disease course in chronic inflammatory demyelinating polyneuropathy 40 and they were reduced in response to immune therapy in inflammatory neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 CCM has proven diagnostic value in diabetic neuropathy, 15 , 16 , 17 hereditary neuropathy, 18 , 19 idiopathic small fibre neuropathy, 20 and immune‐mediated neuropathies. 21 , 22 CCM has also been used to differentiate inflammatory from non‐inflammatory neuropathies based on quantification of cellular infiltrates around the sub‐basal nerve plexus 22 , 23 , 24 and to identify corneal nerve loss in patients with hereditary transthyretin amyloidosis polyneuropathy (ATTRv), 25 particularly avoiding the floor effect of unobtainable sural nerve amplitudes and IENFD. 26 More recently in a study from China, early sub‐clinical loss of corneal nerves had a high diagnostic utility in ATTRv amyloidosis and it also demonstrated immature Langerhans cell clusters at the inferior whorl.…”
Section: Introductionmentioning
confidence: 99%
“…Stettner et al ( 41 ) confirmed and extended these results by showing significant corneal nerve loss and an increase in dendritic cells in a large cohort of patients with CIDP, multifocal motor neuropathy (MMN) and monoclonal gammopathy of unknown significance (MGUS) which was associated with neurologic severity and the presence of pain. Moreover, whilst the extent of corneal nerve fiber loss was comparable, dendritic cell density in proximity to nerve fibers was found to be increased in patients with CIDP compared to diabetic neuropathy ( 42 ).…”
Section: Ccm In Peripheral Neuropathiesmentioning
confidence: 92%